Pleomorphic adenoma in minor salivary glands. Cases series report - Grajeda Cruz, Jonathan Alexis (2021)
Pleomorphic adenoma (PA) is the most common benign tumor of the salivary glands that is characterized by its broad pleomorphic architecture. It represents 53-77% of all salivary gland neoplasms, mainly affecting the major salivary glands; however the minor salivary glands is an infrequent site of occurrence, representing 5-10% of cases, mainly on the palate and lip, nasal cavity, pharynx, larynx and trachea. The confirmatory diagnosis is performed with a histopathological study. The indicated treatment is the wide resection of the tumor. It is essential to know the surgical technique to avoid the recurrence of the disorder. Therefore, the aim of the present paper is to describe three  cases of PA located in infrequent sites of PA, such as the minor salivary glands.